Development of Problem-Based Learnıng-Based Modules on Sequence and Series Material for Grade XI at SMA Negeri Semangus - Saryani, Ririn; Fitriyana, Nur; Elly, As (Jurnal Pendidikan Matematika (JPM), 2024)
This research aims to produce a Mathematics Module based on Problem-Based Learning (PBL) on sequence and series material for grade XI SMA Negeri (State High School) Semangus that is valid, practical, and has potential effects. The research method uses the stages of the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through interviews, observations, questionnaires, and tests, with the research subjects including validators (linguist experts, material experts, and media experts), mathematics teachers, and students of class XI SMA Negeri Semangus. Based on the results of data analysis, it shows that Aiken's V value from the experts obtained a total of 0.90 with a very valid category. In the practicality test, educators and students obtained an overall of 90.16 in the very practical category. The results of the potential effect test through tests given to 30 students showed that 26 students (86.7%) were in the completed category and 4 students (13.3%) were in the incomplete category. So it can be concluded that the PBL mathematics module developed in this research is declared valid, practical, and has potential effects.